2023
DOI: 10.1186/s12913-023-09290-1
|View full text |Cite
|
Sign up to set email alerts
|

How do stroke early supported discharge services achieve intensive and responsive service provision? Findings from a realist evaluation study (WISE)

Abstract: Background Stroke Early Supported Discharge (ESD) involves provision of responsive and intensive rehabilitation to stroke survivors at home and it is recommended as part of the stroke care pathway. Core components have been identified to guide the delivery of evidence-based ESD, however, service provision in England is of variable quality. The study sought to understand how and in what conditions the adoption of these components drives the delivery of responsive and intensive ESD services in re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…5 Our findings reflect recent qualitative research with healthcare professionals in the United Kingdom (n = 117) where therapy assistants were described as having a key role to play in the team and development of an interdisciplinary skillset among therapy assistants helped manage capacity issues. 9 Importantly, this study highlighted the need to empower and promote the autonomy of assistant staff through appropriate supervision and upskilling. 9 Other research has confirmed that therapy assistants can improve capacity and efficiency 22 however to date they may be underutilised within community settings.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…5 Our findings reflect recent qualitative research with healthcare professionals in the United Kingdom (n = 117) where therapy assistants were described as having a key role to play in the team and development of an interdisciplinary skillset among therapy assistants helped manage capacity issues. 9 Importantly, this study highlighted the need to empower and promote the autonomy of assistant staff through appropriate supervision and upskilling. 9 Other research has confirmed that therapy assistants can improve capacity and efficiency 22 however to date they may be underutilised within community settings.…”
Section: Discussionmentioning
confidence: 91%
“…9 Importantly, this study highlighted the need to empower and promote the autonomy of assistant staff through appropriate supervision and upskilling. 9 Other research has confirmed that therapy assistants can improve capacity and efficiency 22 however to date they may be underutilised within community settings. 23 Further research is needed to quantify the benefits and cost implications of therapy assistants as part of Early Supported Discharge teams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding aligns with another Asian study that reported a discharge rate of 76.8% for stroke patients after inpatient rehabilitation [ 48 ]. The high percentage of patients being able to be discharged home can be attributed to improvement in community resources, Asian close-knit family support systems, ready availability of paid live-in caregivers who are employed as foreign domestic caregivers as well as implementation of early discharge planning [ 49 , 50 ]. These initiatives have facilitated a smoother transition from hospital to home and have provided stroke survivors with the necessary support to continue their recovery in a familiar environment.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were recruited from an early supported discharge (ESD) program in Camrose, Alberta, Canada, which has a population of just under 21,000 residents. The ESD program was originally designed to support patients recovering from acute stroke (Chouliara et al, 2023); however, during the COVID-19 pandemic, it was adapted for COVID-19. Patients were referred to the program either directly from hospital (at discharge) or through community clinics.…”
Section: Patient Cohortmentioning
confidence: 99%